Tool-use Extends Peripersonal Space Boundaries in Schizophrenic Patients. (16th June 2022) - Ferroni, Francesca; Ardizzi, Martina; Magnani, Francesca; Ferri, Francesca; Langiulli, Nunzio; Rastelli, Francesca; Lucarini, Valeria; Giustozzi, Francesca; Volpe, Roberto; Marchesi, Carlo; Tonna, Matteo; Gallese, Vittorio
Abstract: Background and Hypothesis: A primary disruption of the bodily self is considered a core feature of schizophrenia (SCZ). The "disembodied" self might be underpinned by inefficient body-related multisensory integration processes, normally occurring in the peripersonal space (PPS), a plastic sector of space surrounding the body whose extent is altered in SCZ. Although PPS is a malleable interface marking the perceptual border between self and others, no study has addressed the potential alteration of its plasticity in SCZ. We investigated the plasticity of PPS in SCZ patients after a motor training with a tool in the far space. Study Design: Twenty-seven SCZ patients and 32 healthy controls (HC) underwent an audio-tactile task to estimate PPS boundary before (Session 1) and after (Session 3) the tool-use. Parameters of PPS, including the size and the slope of the psychometric function describing audio-tactile RTs as a function of the audio-tactile distances, were estimated. Study Results: Results confirm a narrow PPS extent in SCZ. Surprisingly, we found PPS expansion in both groups, thus showing for the first time a preserved PPS plasticity in SCZ. Patients experienced a weaker differentiation from others, as indicated by a shallower PPS slope at Session 1 that correlated positively with negative symptoms. However, at Session 3, patients marked their bodily boundary in a steeper way, suggesting a sharper demarcation of PPS boundaries after the action with the tool. Conclusions: These findings highlight the importance of investigating the multisensory and motor roots of self-disorders, paving the way for future body-centred rehabilitation interventions that could improve patients' altered body boundary.